2015
DOI: 10.1371/journal.pone.0120270
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Risk Factors for Combat-Related PTSD among Military Personnel and Veterans

Abstract: Post-traumatic stress disorder (PTSD), a complex and chronic disorder caused by exposure to a traumatic event, is a common psychological result of current military operations. It causes substantial distress and interferes with personal and social functioning. Consequently, identifying the risk factors that make military personnel and veterans more likely to experience PTSD is of academic, clinical, and social importance. Four electronic databases (PubMed, Embase, Web of Science, and PsycINFO) were used to sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
346
8
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(402 citation statements)
references
References 83 publications
42
346
8
6
Order By: Relevance
“…However, the results suggest that women have an overall increased risk of PTSD. In line with some past research, when the model did not include non-deployment-related trauma, there was a significant effect of gender, where women were more likely to report PTSD (Luxton et al, 2010; Mustillo & Kysar-Moon, 2016; Xue et al, 2015). However, after controlling for non-deployment-related trauma, the gender differences decreased considerably, indicating that non-deployment trauma exposure substantially contributes to gender differences in PTSD.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, the results suggest that women have an overall increased risk of PTSD. In line with some past research, when the model did not include non-deployment-related trauma, there was a significant effect of gender, where women were more likely to report PTSD (Luxton et al, 2010; Mustillo & Kysar-Moon, 2016; Xue et al, 2015). However, after controlling for non-deployment-related trauma, the gender differences decreased considerably, indicating that non-deployment trauma exposure substantially contributes to gender differences in PTSD.…”
Section: Discussionsupporting
confidence: 76%
“…Jacobson, Donoho, Crum-Cianflone, & Maguen, 2015; Maguen, Luxton, Skopp, & Madden, 2012), others report an increased risk of PTSD among women (e.g. LeardMann, Smith, Smith, Wells, & Ryan, 2009; Luxton, Skopp, & Maguen, 2010; Mustillo & Kysar-Moon, 2016; Xue et al, 2015), and one study reported an increased risk of PTSD among men (i.e. Hourani, Willians, Bray, Wilk, & Hoge, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies hitherto have found a relatively consistent positive association between previous deployments and depression, as well as PTSD (Kline et al, 2010; Reger, Gahm, Swanson, & Duma, 2009; Xue et al, 2015). An association between lower rank and higher risk of post-deployment PTSD has also been found (Iversen et al, 2008; Xue et al, 2015). The same is true for female gender, which has consistently been found to be associated with higher risk of post-deployment PTSD (Xue et al, 2015).…”
Section: Methodsmentioning
confidence: 98%
“…Studies have shown that the intensity and frequency of combat exposure are often proportional to post-deployment severity of posttraumatic stress disorder (PTSD) (Fear et al, 2010; Xue et al, 2015). However, life in a war zone often includes stressful experiences not related directly to combat and not posing a direct threat, e.g.…”
Section: Introductionmentioning
confidence: 99%